2020
DOI: 10.1186/s12891-020-03477-x
|View full text |Cite
|
Sign up to set email alerts
|

No differences in cost-effectiveness and short-term functional outcomes between cemented and uncemented total knee arthroplasty

Abstract: Background: There is an ongoing debate regarding optimal fixation of total knee arthroplasty (TKA), however cost has not been addressed as profoundly. Therefore, the current study primarily aimed to compare costs and costeffectiveness 1 year after cemented or uncemented TKA. A secondary objective was to compare short-term functional outcomes between both groups. Methods: A posthoc prospective observational multicenter cohort study of 60 cemented and 50 uncemented Low Contact Stress (LCS) knee systems. Outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…The 6-month EQ-5D was statistically significantly higher in all age groups for cemented TKRs except in the over-75 group. This is in contrast to work by Rassir et al ( 28 ) who found no statistically significant difference in the EQ-5D or cost-effectiveness between cemented and cementless TKRs in a small study. The absolute difference in EQ-5D of 0.02 observed in our study is small, and is lower than 0.03 which is the lower end of the MCID for the EQ-5D index described by Coretti et al ( 29 ) for musculoskeletal related issues.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The 6-month EQ-5D was statistically significantly higher in all age groups for cemented TKRs except in the over-75 group. This is in contrast to work by Rassir et al ( 28 ) who found no statistically significant difference in the EQ-5D or cost-effectiveness between cemented and cementless TKRs in a small study. The absolute difference in EQ-5D of 0.02 observed in our study is small, and is lower than 0.03 which is the lower end of the MCID for the EQ-5D index described by Coretti et al ( 29 ) for musculoskeletal related issues.…”
Section: Discussioncontrasting
confidence: 99%
“…Prasad et al ( 27 ) more recently performed a meta-analysis comparing the midterm outcomes of cemented and cementless TKRs and also found no differences in the Western Ontario and McMaster Universities Osteoarthritis Index or Knee Society Score between groups. Additionally, Rassir et al ( 28 ) in a multicentre study found that the cemented and cementless TKRs did not differ statistically significantly in functional outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Additionally, 90-day readmissions following TJA create an enormous national healthcare economic burden, with approximately half of the annual expenses attributed to readmissions unrelated to the TJA [11,12]. However, improvements in technique and implant positioning may mitigate the costs of revisions [13][14][15][16][17], which are responsible for the greatest readmission, post-acute care, and long-term expenses [12]. With the incidence of revision arthroplasties projected to increase over the next several decades [18,19], there is an impetus to continue optimizing techniques and technologies to reduce revision and readmission rates following primary TJA.…”
Section: Introductionmentioning
confidence: 99%